PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA KRISTEN DENGAN MODEL TALKING STICK PADA MATERI HUKUM BERPACARAN DI KELAS X MIA 2 TAHUN PELAJARAN 2020/2021 SMA NEGERI 1 PADANG BOLAK KABUPATEN PADANG LAWAS UTARA - GELIMA SIMATUPANG (LP2MTBM MAKARIOZ, 2021)
The research aims to find out the extent to which talking stick learning models can improve student learning. The subject ofthis study is students of kela X MIA 2 Sma Negeri 1 Padang Bolak Padang Lawas Utara semester 1 of the 2020/2021 schoolyear which amounted to 20 students. The study took place in two cycles, each of which consisted of stages of planning,action, observation, and reflection. The data obtained in this study include: student learning achievement taken from theprovision of test questions at the end of the cycle, the teacher's ability in learning taken from observation sheets, studentactivities in learning taken from observation, and data on student reflection on learning taken from the questionnaire at theend of each meeting. The results of this study show that Talking stick learning can improve the learning outcomes ofChristian religious education subjects, especially dating law materials for students of class X MIA 2 semester 1 Sma Negeri 1Padang Bolak Padang Lawas Utara School Year 2020/2021. Student learning outcomes must reach KKM which is 75%.Judging from the results on pre-cycle observations of 20 students who had a grade point average of 70.00%. From theresults of the cycle I test, with a grade point average of 76.00%. And cycle II can be known that the average student's gradeis 87.50%. that achieves completion as many as 20 students (100.00%). Then the percentage of student completionincreased from pre-cycle 30.00%, cycle I to 50.00% and cycle II to 100.00% or increased by 20.00%.